Wolbachia infection can bias estimates of intralocus sexual conflict. Issue 1 (26th December 2018) - Duffy, Eoin; Archer, C. Ruth; Sharma, Manmohan Dev; Prus, Monika; Joag, Richa A.; Radwan, Jacek; Wedell, Nina; Hosken, David J.
Abstract: Males and females share most of their genome and develop many of the same traits. However, each sex frequently has different optimal values for these shared traits, creating intralocus sexual conflict. This conflict has been observed in wild and laboratory populations of insects and affects important evolutionary processes such as sexual selection, the maintenance of genetic variation, and possibly even speciation. Given the broad impacts of intralocus conflict, accurately detecting and measuring it is important. A common way to detect intralocus sexual conflict is to calculate the intersexual genetic correlation for fitness, with negative values suggesting conflict. Here, we highlight a potential confounder of this measure—cytoplasmic incompatibility caused by the intracellular parasite Wolbachia. Infection with Wolbachia can generate negative intersexual genetic correlations for fitness in insects, suggestive of intralocus sexual conflict . This is because cytoplasmic incompatibility reduces the fitness of uninfected females mated to infected males, while uninfected males will not suffer reductions in fitness if they mate with infected females and may even be fitter than infected males. This can lead to strong negative intersexual genetic correlations for fitness, mimicking intralocus conflict. We illustrate this issue using simulations and then present Drosophila simulans data that show how reproductive incompatibilities caused by Wolbachia infection can generate signals of intralocus sexual conflict. Given that Wolbachia infection in insect populations is pervasive, but populations usually contain both infected and uninfected individuals providing scope for cytoplasmic incompatibility, this is an important consideration for sexual conflict research but one which, to date, has been largely underappreciated. Abstract : Intralocus sexual conflict has been implicated in numerous evolutionary processes, and one way to detect this conflict is by calculating the intersexual genetic correlation for fitness. We demonstrate that reproductive incompatibilities caused by Wolbachia infection can mimic sexually antagonistic fitness variation and inflate signals of intralocus sexual conflict in Drosophila .